Determinants of Bank Lending in Nepal - Timsina, Neelam (NRB Economic Review, 2016)
Commercial banks constitute a major chunk of total assets in the banking system in Nepal and extension of credit is one of the major functions of banking institutions. If banks are not efficient in their lending behavior, it may not contribute to economic growth. On the other hand, their inefficient and imprudent banking practices may lead to riskier financial instability. The main objective of the study is to test and confirm the effectiveness of the determinants of commercial bank lending behavior in Nepal by using time series Ordinary Least Square regression approach for empirical analysis. The model involves Nepalese commercial banks' private sector credit (pvct) as dependent variable and other variables such as their volume of deposits (dep), interest rate (Ir), stipulated cash reserve requirements ratio (crr), their liquidity ratio (lr), inflation (inf), exchange rate (exr), and gross domestic product (gdp) as independent variables for the period; 1975 – 2014. From the regression analysis, it was found that Gross Domestic Product and liquidity ratio of banks have the greatest impacts on their lending behavior. Granger Causality Test shows the evidence of unidirectional casual relationship from GDP to private sector credit. The study implies that GDP is the barometer of the economy and commercial banks should pay their attention to the overall macro economic situation of the country, factors affecting the GDP in general and their liquidity ratio in particular while taking lending decision.